Laparoscopic sacrocolpopexy versus pelvic organ prolapse suspension for surgical management of pelvic organ prolapse: a retrospective study. (18th August 2022) - Tagliaferri, Valeria; Taccaliti, Chiara; Romano, Federico; D'Asta, Marco; Martulli, Bruno; Gentile, Cosimo; Legge, Francesco; Ruggieri, Stefania; Guido, Maurizio
Abstract: This retrospective surgical clinical study compares clinical and functional effects of laparoscopic sacrocolpopexy (LSC) and laparoscopic pelvic organ prolapse suspension (L-POPS) for anterior and central prolapse correction. Thirty patients enrolled were affected by a symptomatic vaginal central compartment stage 2–3 prolapse and vaginal anterior compartment stage 1–3 prolapse without vaginal posterior compartment prolapse. A successful correction of anterior and central compartments prolapse without relapses were observed in both groups (LSC group versus L-POPS group). In patients who underwent L-POPS, a de novo posterior compartment prolapse was recorded. In this group, 7/15 patients complained more bowel symptoms and underwent vaginal colpoperineoplasty. In 20% (group LSC) and in 13.3% (group L-POPS) of cases, a condition of de novo urinary stress incontinence was described. LSC seems to remain the gold standard for pelvic organ prolapse correction, while further preventive strategies should be carried out in L-POPS to avoid a de novo posterior compartment prolapse. Impact Statement: What is already known on this subject? Laparoscopic sacrocolpopexy is the gold standard technique for the correction of pelvic organ prolapse; however, laparoscopic pelvic organ prolapse suspension, based on the surgical technique of lateral suspension, is an innovative surgical method for the treatment of POP. What do the results of this study add? L-POPS could be considered a valid alternative to LSC for women with multiple comorbidities because of less operative time and reduced surgical risks. However, in the long follow-up period, some patients underwent L-POPS complained rectal discomfort and dysfunction on quality of life questionnaire and on clinical evaluation from six to twelve months after surgery probably due to the post-operative appearance of posterior compartment prolapse. What are the implications of these findings for clinical practice and/or further research? Considering the retrospective design and the small sample size the major limits of this study, larger, prospective, randomized studies could be encouraged to better compare a modified technique of L-POPS with posterior mesh apposition (preventing the post-operative appearance of posterior compartment prolapse) with the gold standard LSC for the correction of multi-compartment POP.